Understanding the Telework Experience of People with Disabilities - Tang, John (CSCW 2021, 2021)
To understand the lived experience of how people with disabilities telework in the United States, 25 people were interviewed. The participants included people who are blind or low vision, deaf or hard of hearing, neurodiverse, have limited mobility/dexterity, and have chronic health issues. The interviews focused on how they used video calling, screen sharing, and collaborative editing technologies to accomplish their telework. The interviews found ways in which design choices made in telework technologies interact with people’s abilities, especially those who are blind or low vision, since the tools rely heavily on the visual channel to enable remote collaboration. A central theme emerged around how design choices made in telework technologies affect the digital representation of people’s online activities in the video call interface: those who turn off their video (because they are blind or do not want to expend the cognitive effort to present themselves over video) are relegated to a static icon on a blank video frame with their name while those who are deaf and speak silently through a sign language interpreter never show up in interfaces that use active speaker detection to choose which video streams to display. Users with disabilities may avoid using screen sharing and collaborative editing tools which “leak” cues that disclose their disabilities. Because the interviews were conducted during the first month of the COVID-19 pandemic response, they also provided a preview of how the sudden shift to pervasive teleworking affected their telework experience.